Initial characterization of an unidentified Armillaria isolate from Serbia using LSU‐IGS1 and TEF‐1‐α genes. Issue 2 (22nd July 2014) - Keča, N.; Klopfenstein, N. B.; Kim, M.‐S.; Solheim, H.; Woodward, S.; Holdenrieder, O.
Summary Armillaria species have a global distribution and play variable ecological roles, including causing root disease of diverse forest, ornamental and horticultural trees. Accurate identification of Armillaria species is critical to understand their distribution and ecological roles. This work focused on characterizing an unidentified Armillaria isolate from a Serbian forest using pairing, sequencing of the partial large subunit and intergenic spacer‐1 regions of rDNA (LSU‐IGS1) and the translation elongation factor‐1 alpha gene (tef‐1α) genes, and phylogenetic analyses. Despite previously obtained LSU‐IGS1 RFLP patterns that matched the newly described North American Armillaria altimontana, pairing tests and phylogenetic analyses of LSU‐IGS1 and tef‐1α sequences clearly demonstrate that the unidentified isolate is not A. altimontana. Based on LSU‐IGS1, Armillaria gallica isolates were polyphyletic, and the Serbian isolate clustered with a subset of European A. gallica isolates within a well‐supported clade (99%). Based on tef‐1α, the Serbian isolate appeared as a separate, well‐supported clade (97%) that was basal to other poorly resolved, polyphyletic clades containing European A. gallica isolates. It is speculated that the unidentified Armillaria isolate from Serbia could represent an evolutionary ancestral state because of its separate, basal position compared with other clades comprising polyphyletic European A. gallica isolates. Alternatively, this unidentified Serbian isolate could represent an unusual hybrid because of its high‐level sequence heterogeneity, represented by multiple two‐nucleotide codes, within tef‐1α. Further characterization is needed to confirm the taxonomic status and ecological/evolutionary significance of this unique, unknown Armillaria isolate from Serbia.